Mack & Rita [videorecording (DVD)] - Paige, Taylour, 1990-; Lail, Elizabeth; Devine, Loretta; Hill, Amy, 1953-; Smith, Lois, 1930-; Malick, Wendie; Harrison, Patti, 1990-; Weyrich, Addie; Carrero, Aimee, 1988-; Byer, Nicole; Rex, Simon, 1974-; Milligan, Dustin (Lionsgate, 2022)
A 30-year-old writer spends a wild weekend in Palm Springs and wakes up to find she has magically transformed into her inner 70-year-old.